LENGTH – WEIGHT RELATIONSHIP OF Heterobranchus longifilis REARED IN EARTHEN PONDS - PEPPLE, P.C.G; OFOR , C. O. (Nigerian Journal of Fisheries, 2011)
Length – weight relationship, condition factor and sex ratio of 90 specimens of Heterobranchus longifilis reared in earthen ponds of Nigerian Institute for Oceanography and Marine Research (NIOMR) integrated fish farm, Ijoyi – Badore were determined. The parameters “a” and “b” of the length – weight relationship were estimated using the formula W = aLb while the condition factor was calculated from the equation, K = 100WL3. The length-weight relationship of H. longifilis showed positive correlation (r = 0.96). The regression exponent for males, females and combined sexes were 3.0168, 3.2429 and 3.0446 respectively. The correlation coefficient “r” for males, females and combined sexes were 0.9354, 0.9474 and 0.9546 respectively. The species showed positive allometric growth. The average “K” value for the males was 0.8282 ± 0.1198, females 0.8266 ± 0.0798 while combined sexes were 0.8275 ± 0.1039. The sex ratio of males to females was 1.31:1 and there was no significant difference from the expected 1:1 ratio at 5% level of significance. The determination of “b” and “K” can be used in growth performance, feed utilization and well being of fish in earthen ponds assessment.